RFID: The Up and Coming Technology - Erick Jones; Shalini Gupta; Joshua Bolton (International Journal of Supply Chain Management, 2015)
Abstract RFID has been the up and coming technology that many manufacturing and warehousing businesses has been delighted to use, while others still analyse the use and cost variables that come with such a technology. This document will serve as an analysis of the use of RFID and the variables that come along with this future of technology. Keywords RFID, variance, cost, technology, simulation.